Comprehensive dosimetric and clinical evaluation of lexicographic optimization-based planning for cervical cancer - Trivellato, Sara; Caricato, Paolo; Pellegrini, Roberto; Montanari, Gianluca; Daniotti, Martina Camilla; Bordigoni, Bianca; Faccenda, Valeria; Panizza, Denis; Meregalli, Sofia; Bonetto, Elisa; Arcangeli, Stefano; De Ponti, Elena (Frontiers in Oncology, 2022)
Aim In this study, a not yet commercially available fully-automated lexicographic optimization (LO) planning algorithm, called mCycle (Elekta AB, Stockholm, Sweden), was validated for cervical cancer. Material and Methods Twenty-four mono-institutional consecutive treatment plans (50Gy/25fx) delivered between November 2019 and April 2022 were retrospectively selected. The automatic re-planning was performed by mCycle, implemented in the Monaco TPS research version (v5.59.13), in which the LO and Multicriterial Optimization (MCO) are coupled with Monte Carlo calculation. mCycle optimization follows an a-priori assigned priority list, the so-called Wish List (WL), representing a dialogue between the radiation oncologist and the planner setting hard constraints and following objectives. The WL was tuned on a patient subset accordingly to the Institution’s clinical protocol to obtain an optimal plan in a single optimization. This robust WL was then used to automatically re-plan the remaining patients. Manual plans (MP) and mCycle plans (mCP) were compared in terms of dose distributions, complexity (modulation complexity score, MCS), and delivery accuracy (perpendicular diode matrices, gamma analysis-passing ratio, PR). Their clinical acceptability was assessed through the blind choice of 2 radiation oncologists. Finally, a global quality score index (SI) was defined to gather into a single number the plan evaluation process. Results The WL tuning requested 4 patients. The 20 automated re-planning took 3 working days. The median optimization and calculation time can be estimated at 4 hours and just over 1 hour per MP and mCP, respectively. The dose comparison showed a comparable organ-at-risk sparing. The planning target volume coverage increased (V95%: MP 98.0%[95.6–99.3]; mCP 99.2%[89.7–99.9], p>0.05). A significant increase has been registered in MCS (MP 0.29[0.24–0.34]; mCP 0.26[0.23–0.30], p<0.05) without affecting delivery accuracy (PR(3%/3mm): MP 97.0%[92.7–99.2]; mCP 97.1%[95.0–98.6], p>0.05). In the blind choice, all mCP resulted clinically acceptable and chosen over MP in more than 75% of cases. The median SI score was 0.69[0.41–0.84] and 0.73[0.51–0.82] for MP and mCP, respectively (p>0.05). Conclusions mCycle plans were comparable to clinical manual plans, more complex but accurately deliverable and registering a similar SI. Automated plans outperformed manual plans at the blinded clinical choice.